Exploring the impacts of transformational supervision on supermarket store managers' creativity: evidence from Nigeria, South Africa, and the United Kingdom. Issue 2 (3rd April 2022) - Alo, Obinna; Cooper, Sir Cary; Arslan, Ahmad; Tarba, Shlomo
Abstract: The current article is one of the rare studies to specifically focus on the contextual conditions under which the learning-related actions of transformational supervisors' help retailing supermarkets' store managers to learn and engage in behaviors that produce creative outcomes. We use a qualitative research approach with the data based on in-depth semi structured interviews with 40 retailing supermarkets' store managers in Nigeria, South Africa and the UK. Our findings show that transformational supervision significantly boosts store managers' creativity, facilitated by fostering store managers' learning orientation, creative role identity (CRI) and creative self-efficacy (CSE), in all three contexts. From our findings, we have developed a model that symbolize the role of transformational supervisors in fostering store managers' creativity, which provides a baseline for supermarkets in (re)evaluating the significance of their leadership styles on follower creativity.